The Wiley Blackwell companion to tourism - Hall, Colin Michael, 1961- (Wiley-Blackwell, 2024)
"The Wiley Blackwell Companion to Tourism 2nd edition aims to offer the first authoritative overview of tourism studies following the COVID-19 pandemic, after the dust has settled and the longer-term impacts can be assessed. It is edited by a leading figure with chapters written by an international team of top scholars to provide essential reading for students and researchers. The new edition incorporates diverse theories, core themes, major perspectives, and new developments. It explores the organization and practice of tourism, as well as key health, economic, social, and environmental issues. It addresses the impact of the COVID-19 pandemic on tourism and the tourist industry, reflecting complexity and change in the field while offering clarity and accessibility for students"-- Provided by publisher.
Collection of essays by Judit Zoltan and others.
Keywords: Tourism -- Handbooks, manuals, etc.; elektronické knihy; electronic books